A configurational analysis of the termination scenarios of international joint ventures: All is well that ends well; Un análisis configuracional de escenarios de terminación de joint ventures internacionales - Ursula F. Ott; David Williams; James Saker; Lee Staley (Journal of Innovation & Knowledge (JIK), 2019)
This article analyzes termination in international joint ventures (IJVs) with a set theoretic approach and fuzzy set Qualitative Comparative Analysis (fsQCA) to show that parent contribution, ownership, managerial configuration and experience can lead to a successful end of a joint venture. The use of fsQCA provides the causal paths leading to termination. Termination by achieving the objectives and termination by corporate restructuring are the most common ways in IJVs to end the collaborative venture and are a consequence of the joint set of foreign contribution, ownership structure, managerial configuration and experience. The duration of terminated IJVs highlights the importance of managerial experience and local contribution.
Keywords: C78; D8; F5; 650; Automotive industry; Empresas conjuntas internacionales; fuzzy set Qualitative Comparative Analysis (fsQCA); International joint ventures; Termination strategies